Students’ Resistance towards Morality-based Recurriculation - Mohlake, Mosimaneotsile (South African Journal of Higher Education, 2016)
In the words of Martin Luther King Jnr, because of the type of education we offer, now “we have learned to fly the air like birds and swim the sea like fish, but we have not learned the simple art of living together as brothers…. We have guided missiles and misguided man”. The irrefutable existence of such misguided yet educated persons may be seen through the unfortunate presence of white-collar amoral incidences throughout the world. From academia to business, politics to religious institutes, humane behaviour in Africa leaves much to hope for. This is despite the fact that historical records and -first-world countries and third-world countries is neither the availability of natural resources nor the age of the country, but rather the inculcation of morality-related skills such as punctuality and healthy work-ethic. However, when such skills are treated only as concepts rather than skills, their efficacy cannot translate into progressive development. This paper reports on a small-scale study done at the University of Limpopo that sought Extended Curriculum students’ opinion on morality-based revamped curriculum which factored in a Life Skills foundational provision. Intimations shall be made vis-à-vis the inclusion of pro-development morals within higher education curricula.